2022
DOI: 10.1002/jsfa.12004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of potassium salts on the structure of γ‐cyclodextrin MOF and the encapsulation properties with thymol

Abstract: BACKGROUND: Thymol is a natural essential oil with strong volatility, low solubility, poor dispersion, strong irritation, and an unpleasant smell, which often requires appropriate porous materials to encapsulate thymol during the application process. However, the encapsulation efficiency of thymol in inclusion complexes is low, and new methods of encapsulation need to be developed. In the present study, the encapsulation capacity, storage stability, and antibacterial activity of thymol were investigated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Presumably, γ-CD-MOF is more suitable for thymol encapsulation due to its matched cavity diameter with the dimension of this aroma molecule. Our previous study has found that γ-CD-MOF (prepared by KOH) showed regular cubic crystalline structures with smooth and particle surfaces [ 31 ]. Generally, the hydrophobic cavity of cyclodextrin and newly formed pores between cyclodextrin molecules are two types of cavity structures that exist in CD-MOF crystals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Presumably, γ-CD-MOF is more suitable for thymol encapsulation due to its matched cavity diameter with the dimension of this aroma molecule. Our previous study has found that γ-CD-MOF (prepared by KOH) showed regular cubic crystalline structures with smooth and particle surfaces [ 31 ]. Generally, the hydrophobic cavity of cyclodextrin and newly formed pores between cyclodextrin molecules are two types of cavity structures that exist in CD-MOF crystals.…”
Section: Resultsmentioning
confidence: 99%
“…The cavity size of α-, β-, and γ-CDs increases gradually, and the newly formed cavity size is closely related to the length of the K−O bond and the arrangement of CD molecules [ 42 ]. Studies have shown that the monoclinic space group crystallizes α-CD-MOF and β-CD-MOF, and the diameter of the intermolecular cavity is about 0.5 nm [ 29 , 42 ], while γ-CD-MOF is crystallized in a cubic space group with high symmetry [ 31 ], and cavities are found in the structure with diameters of 1.7 nm, 1.0 nm, and 0.4 nm [ 31 , 41 ]. Thymol binds to CD-MOF through hydrophobic interactions and van der Waals forces [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrothermal synthesis 2. Crystal transformation Valsartan 33.5% 30.2% Ding et al ( 2019 ) CD-MOF γ-CD KOH K + Vapor diffusion Scutellarin 30.42% Zhao et al ( 2020b ) γ-CD-MOF γ-CD KNO 3 K + Vapor diffusion Menthol ~ 11% Hu et al ( 2021 ) KAc-γ-CD-MOF-THY-HT KOH-γ-CD-MOF-THY-HT KCl-γ-CD-MOF-THY-HT γ-CD KAc KOH KCl K + Hydrothermal Thymol 293.8 mg/g 287.7 mg/g 249.3 mg/g Pan et al ( 2022 ) β-CD-MOF β-CD Na 2 C 2 O 4 Na + Solvothermal 5-Fluorouracil 23.02% Lu et al ( 2015 ) β-CD-MOF-1 β-CD-MOF-2 β-CD CsCl Cs + Template-induced approach 5-Fluorouracil Methotrexate 5-Fluorouracil Methotrexate 1.379 g/g 0.689 g/g 1.510 g/g 1.217 g/g Liu et al ( 2017c ) β-CD-MOF β-CD KOH K + …”
Section: Potential Applications Of Cyclodextrin-based Metal–organic F...mentioning
confidence: 99%